High-temperature Corrosion of T22 Steel in N2/H2S-mixed Gas - Kim, MinJung (Advances in Technology Innovation, 2017)
ASTM T22 steel (Fe-2.25Cr-1Mo in wt.%) was corroded at 600 and 700 oC for 5-70 h under an atmospheric pressure that consisted of N2-(0.5. 2.5)%H2S-mixed gas. T22 steel corroded rapidly, forming outer FeS scales and inner (FeS, FeCr2O4)-mixed scale. The formation of the outer FeS scale facilitated the oxidation of Cr to FeCr2O4 in the inner scales. Since the nonprotective FeS scale was present over the whole scale, T22 steel displayed poor corrosion resistance.